(untitled) (Research in Agriculture Livestock and Fisheries, 2017)
Role of chitosan powder on the production of quality rice seedlings of BRRI dhan29 was examined in the field of Sher-e-Bangla Agricultural University, Dhaka. There were six treatments and three replications in the experiment. The treatments were as follows: T1 = 100 g chitosan (CHT) powder/m2, T2 = 200 g CHT powder/m2, T3 = 300 g CHT powder/m2, T4 = 400 g CHT powder/m2, T5 = 500 g CHT powder/m2, T6 = 0 g CHT powder/m2. A significant variation was observed in the seedlings height, biomass production, dry matter production and chemical properties of the seedbed soils due to the application of chitosan powder in the seedbed. The maximum seedlings height, fresh weight, oven dry weight was observed in the treatment T4 and the minimum level in the treatment T6 (control). On the other hand, the maximum level of organic carbon, organic matter and soil pH was recorded in the treatment T5 and the minimum level in the treatment T6 (control). Chitosan powder increased the level of organic matter in a dose dependent manner. Quality of the Boro rice seedlings were improved due to the application of chitosan powder and the seedlings strength were increased in a dose dependent manner. All the treatments were produced good quality Boro rice seedlings having more chlorophyll level and seedlings strength than the control treatments. Our results indicated that treatment T4 shows the superior results than other treatments. These results could be due some nature of soil alkalization and other some macro-micro nutritional supplementation which may be improving the strength of the seedlings. Taken together, chitosan powder could play a significant role in the quality Boro rice seedling production that might be help to increase the grain yield. Res. Agric., Livest. Fish.4(3): 141-149, December 2017